Adipocyte Death Preferentially Induces Liver Injury and Inflammation Through the Activation of Chemokine (C‐C Motif) Receptor 2‐Positive Macrophages and Lipolysis. Issue 5 (18th March 2019) - Kim, Seung‐Jin; Feng, Dechun; Guillot, Adrien; Dai, Shen; Liu, Fengming; Hwang, Seonghwan; Parker, Richard; Seo, Wonhyo; He, Yong; Godlewski, Grzegorz; Jeong, Won‐Il; Lin, Yuhong; et al.
Abstract : Adipocyte death occurs under various physiopathological conditions, including obesity and alcohol drinking, and can trigger organ damage particularly in the liver, but the underlying mechanisms remain obscure. To explore these mechanisms, we developed a mouse model of inducible adipocyte death by overexpressing the human CD59 (hCD59) on adipocytes (adipocyte‐specific hCD59 transgenic mice). Injection of these mice with intermedilysin (ILY), which rapidly lyses hCD59 expressing cells exclusively by binding to the hCD59 but not mouse CD59, resulted in the acute selective death of adipocytes, adipose macrophage infiltration, and elevation of serum free fatty acid (FFA) levels. ILY injection also resulted in the secondary damage to multiple organs with the strongest injury observed in the liver, with inflammation and hepatic macrophage activation. Mechanistically, acute adipocyte death elevated epinephrine and norepinephrine levels and activated lipolysis pathways in adipose tissue in a chemokine (C‐C motif) receptor 2‐positive (CCR2 + ) macrophage‐dependent manner, which was followed by FFA release and lipotoxicity in the liver. Additionally, acute adipocyte death caused hepatic CCR2 + macrophage activation and infiltration, further exacerbating liver injury. Conclusion: Adipocyte death predominantly induces liver injury and inflammation, which is probably due to the superior sensitivity of hepatocytes to lipotoxicity and the abundance of macrophages in the liver.